Characterization of Deep Eutectic Solvents for Dispersive Liquid–Liquid Microextraction for Phenolics. (22nd September 2017) - Ma, Wanwan; Tang, Weiyang; Row, Kyung Ho
ABSTRACT: Dispersive liquid–liquid microextraction using deep eutectic solvents, as novel extraction solvents, was developed for the separation, preconcentration, and determination of chlorophenol, 2, 3-dihydroxybenzoic acid, p -cresol, 4-chlorophenol, 2, 4-dichlorophenol, and 2, 4, 6-trichlorophenol in vegetable oil. Seven deep eutectic solvents composed of choline chloride and different hydrogen bond donors (ethyl glycol, glycerol, 1, 2-butanediol, 1, 4-butanediol, 1, 6-hexanediol, urea, and acetic acid) were characterized. The deep eutectic solvents formed by choline chloride-1, 6-hexanediol in a 1:2 molar ratio provided the highest extraction efficiency. The sonication time, deep eutectic solvent volume, and disperser solvent were optimized. Under the optimal conditions of a sonication time of 11 min, a deep eutectic solvent volume of 90 µL, and acetone as the disperser solvent, extraction recoveries from 76.1 to 88.3% were obtained with 8.46 to 9.46 enrichment factors and the limits of detection exceeding 0.1 µg/mL with the relative standard deviations from 1.0 to 3.5%. This method using dispersive liquid–liquid microextraction with deep eutectic solvents is simple and provides high enrichment.